Redesign of elderly beds as an effort to overcome degenerative diseases using a participatory approach - Dahlan, Muhammad; Ahmad, Arfandi; Pawenari, Andi; Fole, Asrul (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
The utilization of beds among the elderly, especially those with degenerative diseases, presents health and comfort challenges. To address these issues, this research aims to redesign elderly beds using a participatory ergonomics method at Madania Potonoro Nursing Home. By involving the elderly and caregivers in the process, the research findings highlight the need for bed improvements. The proposed design includes additional features such as a folding table, bookshelf, cane holder, assistive standing devices, and a drink holder, based on identified needs. Anthropometric dimensions, including Shoulder Width (SW), Height (H), Popliteal Height (PH), Elbow Height in Sitting (EHS), Elbow Height in Standing (EHS), Seat Depth (SD), and Maximum Grip Diameter (MGD), serve as guidelines for bed design. Analyzing these dimensions at the 5th, 50th, and 95th percentiles, adjustments are made to accommodate additional attributes or features on the bed. The recommended design not only provides optimal comfort and safety for the elderly but also improves their overall quality of life. This research emphasizes the importance of involving users in the design process to ensure solutions align with their needs and preferences.